Endometrial uNK cell counts do not predict successful implantation in an IVF population. Issue 12 (11th December 2019) - Donoghue, J F; Paiva, P; Teh, W T; Cann, L M; Nowell, C; Rees, H; Bittinger, S; Obers, V; Bulmer, J N; Stern, C; McBain, J; Rogers, P A W
Abstract: Study question: Are uterine natural killer (uNK) cell numbers and their distribution relative to endometrial arterioles altered in women with recurrent implantation failure (RIF) compared to women with embryo implantation success (IS)? Summary answer: uNK cell numbers and their distribution relative to endometrial arterioles are not significantly different in women with RIF compared to women in whom embryo implantation occurs successfully following IVF. What is already known: uNK cells are regulators of decidual angiogenesis and spiral arteriole remodelling during early pregnancy. Although some studies have shown that uNK cell numbers may be altered in women with RIF, the methods used to measure uNK cell numbers have proven inconsistent, making reproduction of these results difficult. It is unclear, therefore, whether the results reported so far are reproducible. Moreover, it is not known how uNK cell numbers may impact IVF outcomes. Despite the lack of conclusive evidence, uNK cell numbers are often evaluated as a prognostic criterion in women undergoing assisted reproductive procedures. Study design, size, duration: Endometrial pipelle biopsies were collected 6–8 days post-LH surge in natural cycles from women with RIF ( n = 14), women with IS ( n = 11) and women with potential RIF at the time of the study (PRIF; n = 9) from 2013 to 2015. Participants/materials, setting, methods: uNK cells (i.e. CD56+ and/or CD16+ phenotypes) and their distribution relative to endometrial arterioles were investigated by standard immunohistochemistry protocols and quantified using Aperio ScanScopeXT images digitized by ImageJ and deconvoluted into binary images for single cell quantification using a Gaussian Blur and Yen algorithm. Main results and the role of chance: There was no significant difference in the cell density of CD56+ or CD16+ uNK cells in women with RIF compared to women with IS or PRIF. There was a higher proportion of uNK cells in the distal regions compared to the regions closest to the arterioles in all patient groups. Further, we identified a significant reduction in uNK cell density in women who had a previous pregnancy compared to those who had not, regardless of their current implantation status. Large scale data: Not applicable. Limitations, reasons for caution: Spiral arterioles could not always be accurately identified by digital image analysis; therefore, all endometrial arterioles were selected and analysed. Patient numbers for the study were low. However, as the clinical phenotypes of each patient were well defined, and endometrial dating was accurately determined by three independent pathologists, differences between patient groups with respect to the uNK numbers and distribution should have been measurable if uNK cell counts were to be useful as a prognostic marker of RIF. Wider implications of the findings: Our findings demonstrate that CD56+ and CD16+ uNK cell numbers are not significantly different in women with RIF in a typical cohort of women undergoing IVF. Further, prior pregnancy was associated with a significantly reduced number of uNK cells in both the RIF and IS patient groups, suggestive of a long-term pregnancy induced suppression of uNK cells. Combined, these findings do not support the clinical value of using uNK cell numbers as a prognostic indicator of implantation success with IVF treatment. Study funding/competing interest(s): Funding for this work was provided by Royal Women's Hospital Foundation. P.P. was supported by an NHMRC Early Career Fellowship [TF 11/14] and W.T.T. was supported by an NHMRC Postgraduate Scholarship [1055814]. The authors do not have any competing interests with this study.